PENGARUH BENTUK SUDU IMPELLER BERBEDA TERHADAP TEKANAN PADA LUAS PENAMPANG SUCTION DAN DISCHARGE PADA POMPA SENTRIFUGAL MENGGUNAKAN SIMULASI CFD SOLIDWORKS FLOW SIMULATION - Suliono; Ghozali, Muhamad; Hidayatulloh, Deni (JURNAL REKAYASA ENERGI, 2023)
A device or machine to move fluid fluids or increase fluid pressure. Centrifugal pump is one of the many types of pumps with different ways of working. Centrifugal pumps work by applying centrifugal force to the impeller to suck liquid. This centrifugal force causes vacuum pressure at the suction/inlet and increases the liquid pressure at the discharge/outlet of a liquid. CFD simulation testing and analysis using SOLIDWORKS software to determine variations in physical values such as pressure, discharge, speed and others when modifying parts of the 3D pump model being tested. The results of the first test obtained the highest discharge and torque values of 4 l/s and 1.08 Nm, the second test the discharge and torque decreased to 2.4 l/s and 0.54 Nm and the suction speed increased to 10.88 m/s. In the 3rd test, the outlet pressure rose to 127000 Pa, the speed rose to 7.6 m/s, the torque decreased by 0.17 Nm, and the discharge decreased to 1.69 l/s.